Preparation of Granular Cold Water-Soluble Sago Starch: A Preliminary Study. - Bhupinder, Kaur; Abdul Karim, Alias; Norziah, Mohd Hani; Chee, Choon Seow (Universal Academy Press Inc, 2002)

(untitled)
Granular cold water-soluble (GCWS) sago starches were prepared by treating native sago starch with mixtures of aqueous solutions of ethanol and NaOH at different temperatures.